KARAKTERISTIK SOSIO-DEMOGRAFI IBU TERHADAP PROPORSI PEMBERIAN ASI EKSKLUSIF PADA BALITA USIA DIATAS 6 BULAN HINGGA 24 BULAN DI DESA PEKUTATAN, KECAMATAN PEKUTATAN, KABUPATEN JEMBRANA BALI TAHUN 2015 - Jeevitra Gunasegaran; Putu Ardinata; Gythrie Kartikason (DiscoverSys Inc., 2016)
National coverage of exclusive breastfeeding in 2010 amounted to 15.3%, has not reached the national target of 80%. UNICEF said that as many as 30,000 infant deaths in Indonesia and 10 million deaths of children under five in the world each year could be prevented through breastfeeding (breastfeeding) exclusively for six months from birth without having to provide additional food and drink to the baby.1 Provides energy and nutisi needed by infants during the first months of life and continued until the age of 2 years.2This study used a cross-sectional descriptive design. Samples are mothers who have children ages 6 months to 24 months are taken by using simple random sampling that total of 52 peoples. This research was conducted in the Pekutatan village, Pekutatan subdistrict, Jembrana regency, in November 2015. The data was collected using a questionnaire. The data was analyzed by univariate and bivarite then presented in tabular form.Results and conclusions of this study was the proportion of exclusive breastfeeding at 30.8 percent. The proportion of exclusive breastfeeding in infants aged 6-24 months based on the knowledge level that is equal to 80.2% good category, the largest age exclusive breastfeeding is above 18-30 years (76.9%), the highest parity namely the category of less than 2 (63.5%), ie the highest husband support both categories (53.8%), and the support of most health workers are good category (78.8%).Â